The Impact of Covid-19 on Indonesia's Financial System Stability Using ARIMA Intervention Analysis - Dyah Makutaning Dewi, Dyah Makutaning Dewi; Alvian Ferrandy, Alvian Ferrandy; Nur Aini, Nur Aini; Nasrudin, Nasrudin (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
The financial system has an important role to play in helping the relocation of funds. If the financial system is in unstable condition it will disrupt production, consumption, and investment activities. Then, if financial institutions and financial markets that have a role as financial mediators are facing uncertainty, as a result the allocation of funds will not go well. Therefore, the financial system is strongly related to exchange rates and stocks. On March 2, 2020, the first case of Covid-19 occurred in Indonesia. As a result, the rupiah depreciated and in addition to impacting indonesia's weakening financial market conditions. Capital markets in Indonesia suffered a significant crash marked by a decline IHSG. The purpose of this research is to analyze the impact of Covid-19 on exchange rate movements and IHSG. This research uses the ARIMA intervention method. The results of the analysis showed the negative impact of Covid-19 on the stability of the financial system in Indonesia began to be felt after two weeks of confirmation of the first case. The depreciation of the rupiah is out of the ordinary since the 18th day and IHSG occurred since the 16th day after the announcement of the first case and temporary. Keywords: Covid-19, Exchange Rate, JCI, Financial Stability, Arima Intervention